2017
DOI: 10.1101/101576
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Long-term genomic coevolution of host-parasite interaction in the natural environment

Abstract: The antagonistic coevolution of parasite infectivity and host resistance alters the biological functionality of species, with effects spanning to communities and ecosystems. Still, studies describing long-term host-parasite coevolutionary dynamics in nature are largely missing.Furthermore, the role of host resistance mechanisms for parasite evolution is poorly understood, necessitating for the molecular and phenotypic characterization of both coevolving parasites and their hosts. We combined long-term field sa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
51
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(56 citation statements)
references
References 67 publications
4
51
1
Order By: Relevance
“…In light of the growing interest in understanding the role phages play in host-associated microbiomes, it is imperative that we study the impact of phages on bacterial ecology and evolution within their natural environments. There is reason to predict that knowledge gained from laboratory studies will not clearly translate to natural patterns, as in vitro studies that aim to incorporate more ecological realism consistently find that increasing complexity critically changes bacteria-phage interactions (Gómez and Buckling 2011;Jończyk et al 2011;Gómez et al 2015;De Sordi et al 2017;Laanto et al 2017;Wang et al 2017). We set out to test the impact of phages on evolution of an agriculturally relevant bacterial pathogen, P. syringae, based in part on ex-panding industry interest in using phages as biocontrol in this system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In light of the growing interest in understanding the role phages play in host-associated microbiomes, it is imperative that we study the impact of phages on bacterial ecology and evolution within their natural environments. There is reason to predict that knowledge gained from laboratory studies will not clearly translate to natural patterns, as in vitro studies that aim to incorporate more ecological realism consistently find that increasing complexity critically changes bacteria-phage interactions (Gómez and Buckling 2011;Jończyk et al 2011;Gómez et al 2015;De Sordi et al 2017;Laanto et al 2017;Wang et al 2017). We set out to test the impact of phages on evolution of an agriculturally relevant bacterial pathogen, P. syringae, based in part on ex-panding industry interest in using phages as biocontrol in this system.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have examined bacteria-phage (co)evolution in vivo (Capparelli et al 2006;Meaden and Koskella 2017;Wang et al 2017;De Sordi et al 2018), and none have directly compared the outcome of serially passaged bacteria and phage in vitro and in vivo. However, a growing body of work has focused on understanding bacteria and phage dynamics in ecologi-cally relevant conditions (Gómez and Buckling 2011;Laanto et al 2017;Scanlan et al 2019). For example, recent work investigating Vibrio cholerae phage replication in aquatic environments found that two of three clinically isolated phages had some level of replication in estuarine water, but none were able to replicate in fresh water (Silva-Valenzuela and Camilli 2019).…”
mentioning
confidence: 99%
“…Synthetic co-cultures are well known to also mutually benefit from the cross-feeding of organic acids and nutrients (e.g., McCully et al, 2017) and various individualbased modelling approaches are developed to predict the individuals' competition for process control (Friedman et al, 2017;Daly et al, 2018). Additionally, predator-prey relationships contribute to microbial assembly dynamics, such as the bacterial predator Bdellovibrio spp., which feeds on gram-negative bacterial species (Johnke et al, 2014), or host-parasite relationships in which genotypespecific phages change community structures (Laanto et al, 2017). All these deterministic niche differentiation mechanisms ultimately lead to equilibria, corresponding to a steady-state climax community (Morris and Blackwood, 2007;Nemergut et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…To test these hypotheses, we performed a time-shift experiment that evaluates the resistance of bacterial samples over time against phage from past, concurrent, and future time points [29,30]. We repeated the experimental setup used in Figures 1F (mono-spacer founder F) and 1G (multi-spacer founder C), collecting 12 surviving colonies at 24h, 36h, and 48h post-infection and isolating and amplifying phage from each of them Finally, each colony and their founders were grown in liquid cultures and used to seed top agar media, on which 2 µl of stock phage (which has not co-evolved with CRISPR-resistant staphylococci and was used to obtain the "time zero" datapoint) or phage isolated from each colony was spotted.…”
Section: Host-phage Co-evolution Within Multi-spacer Colonies Leads Tmentioning
confidence: 99%